PROBLEMATIKA PENDIDIKAN ANAK USIA DINI DI INDONESIA - Asep Saepudin (UPI Kampus Cibiru, 2013)
This paper aims to explore education, especially education early childhood, which is one form of educational reform. Educational reform should be oriented on increasing the quality of human resources (HR) quality in accordance with the needs of the working world with the development of technology and able to compete in a globalized world and biting.If you want to create and develop the nation's air-quality, intelligent, faithful and pious and virtuous it should begin from early childhood education. Early Chilhood Education aims to develop a range of potential since early childhood as a preparation for life and can adapt to its environmentTo realize the goal of education, especially early childhood education in Indonesia is still confronted her on issues, among others: the weak economy, low-quality care, parental intervention program low, low quality of early childhood, early childhood less quantity, and low-quality early childhood educators. The problems that must be addressed by doing participatory approaches from various parties. Key word: human resources quality, educators, the problem of early childhood